Rusové v Karlových Varech očima místních obyvatel - Čepelák, Václav (Lidé města, 2010)
The article is a study of the Russian presence in Karlovy Vary from the point of view of its inhabitants’. This presence is described from the viewpoint of the inhabitants’ perception and attitudes towards Russians. The causes of the presence of Russians in Karlovy Vary are also studied; causes are sought in the town’s history, especially in the context of the new colonization of border regions after 1945. The present is described in terms of statistical data, especially that regarding migration and the number of foreigners. The consequences of the Russian presence are found in changes in the urban zoning of the town, as well as in the relation between the Russian presence and the identity of local denizens. The interpretation of nine qualitative interviews provides the source of evidence for this.